2020
DOI: 10.1002/per.2303
|View full text |Cite
|
Sign up to set email alerts
|

Bringing Back the Person into Behavioural Personality Science Using Big Data

Abstract: Behaviour and the individual person are important but widely neglected topics of personality psychology. We argue that new technologies to collect and new methods to analyse Big (Behavioural) Data have the potential to bring back both more behaviour and the individual person into personality science. The call for studying the individual person in the history of personality science, the related idiographic/nomothetic divide, as well as attempts to reconcile these two approaches are briefly reviewed. Furthermore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 136 publications
(401 reference statements)
0
18
0
Order By: Relevance
“…(see also Barbot et al, 2020, Renner et al, 2020. With these developments converging, this may finally be the moment for a proactive revision of psychological theories with the goal of reaching truly personalized descriptions, and in the long run, personalized treatments.…”
Section: Personalized Descriptions and Predictions Require Person-oriented Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…(see also Barbot et al, 2020, Renner et al, 2020. With these developments converging, this may finally be the moment for a proactive revision of psychological theories with the goal of reaching truly personalized descriptions, and in the long run, personalized treatments.…”
Section: Personalized Descriptions and Predictions Require Person-oriented Methodsmentioning
confidence: 99%
“…It may surprise how many established, much-cited psychological theories still predominantly use between-person methods to study within-person patterns, considering the many years of debates about the limitations of between-person methods (e.g., Asendorpf, 2000) and the number of available within-person approaches (e.g., Barbot et al, 2020;Fleeson, 2004;Molenaar, 2004;Renner et al, 2020;Reitzle & Dietrich, 2019;Beck & Jackson, 2021). Some research areas have widely adopted some (but not all) within-person methods described above.…”
Section: Appendix Appendix A: Limitations In the Currently Available Within-person Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We argue that by adopting an idiographic, machine learning-based prediction approach that incorporates information about persons, situations, and time relative only to a single person's experience will allow us to accurately predict future behavior and experiences (Renner, Klee, & von Oertzen, 2020). In the clinical psychology domain, previous research has indicated that future behaviors, like smoking (Fisher & Soyster, 2019) and food craving (Butter et al, 2020) (1) can be predicted with high levels of accuracy using these methods and (2) that the degree of predictability and the important features across people vary considerably.…”
Section: The Present Studymentioning
confidence: 99%